Plant–arthropod interactions in gymnosperm leaves from the Early Permian of Patagonia, Argentina - Gallego, Julieta (2014)
Evidence of plant–arthropod interactions in three orders of gymnosperms is documented in at least five localities from Lower Permian strata of the Río Genoa Formation (Patagonia, Argentina). Arthropod damages were identified in Glossopteris, Gangamopteris, Cordaites and Gingkoites leaves, corresponding to four interactive categories: margin feeding, hole feeding, surface feeding, and oviposition. In addition, a Permian insect trace not previously recorded is described on Glossopteris wilsonii leaves. The diversity of arthropod damage is consistent with the diverse flora of the Río Genoa Formation. In turn, the patterns of arthropod and plant–arthropod interaction provide constraints on the ecology and paleoclimate of Western Gondwana during the Early Permian.